Direct Reprogramming of Mouse Fibroblasts to Osteoblast-like Cells Using Runx2/Dlx5 Factors on Engineered Stiff Hydrogels - Zhang, Junwei; Wang, Yao; Guo, Jing; Zhang, Nihui; He, Jing; Zhou, Zongke; Wu, Fang (ACS applied materials & interfaces, 2023)
Direct reprogramming of somatic cells into functional cells still faces major limitations in terms of efficiency and achieving functional maturity of the reprogramed cells. While different approaches have been developed commonly based on exploiting biochemical signals, introducing appropriate mechanical cues that stimulate the reprogramming process is rarely reported. In this study, collagen-coated polyacrylamide (PAM) hydrogels with stiffness close to that of collagenous bone (40 kPa) were adopted to augment the direct reprogramming process of mouse fibroblasts to osteoblastic-like cells. The results suggested that culturing cells on a hydrogel substrate enhanced the overexpression of osteogenic transcription factors using nonviral vectors and improved the yield of osteoblast-like cells. Particularly, a synergistic effect on achieving osteogenic functionality has been observed for the mechanical cues and overexpression of transcriptional factors, leading to enhanced osteogenic transformation and production of bone mineral matrix. Animal experiments suggested that reprogramed cells generated on matrix hydrogels accelerated bone regeneration and stimulated ectopic osteogenesis. Mechanism analysis suggested the critical involvement of actomyosin contraction and mechanical signal-mediated pathways like the RhoA-ROCK pathway, leading to a synergistic effect on the key transcriptional processes, including chromatin remodeling, nuclear translocation, and epigenetic transition. This study provides insights into the mechanical cue-enhanced direct reprogramming and cell therapy.